Experiences and Partnership Expectation Women and Midwife in Midwifery Care: A Review of Qualitative Study Systhematic - Rizky Vaira (Alma Ata University Press, 2019)
The partnership of Midwives and women is the philosophy of Midwifery care in the period of decline, which occurred the violence and not mutually appreciated especially during childbirth in developing countries. The aim to explore the experiences of women and Midwives, strategy and expectation of women and Midwives in Midwifery services. This study using electronic methods Searches of PubMed bibliographic database, ScienceDirect, Proquest is done systematically from 2008 to 2018. Quality Articles are chosen based on the criteria of inclusion and extracting results from article 858 into 10 Articles, and then classify the comparison results to developing countries and developed countries. Based on the results of the review found the experience of women and Midwives for care in developing countries less well Because there is no Accompanying childbirth, there is physical or verbal violence, and hospital facilities that do not support. While the experience of women in developed countries and Midwives Midwives, either Because the present critical period in time, there is a sense of care from Midwives who Become partners for women. Partnership Midwives and women since pregnancy Contribute to vaginal birth. Midwives and women have hope that Midwifery services can be given a maximum, qualified and manifested a sense of mutual understanding and respect for each other. The condition of Midwifery care in developing countries need particular attention. The importance of the presence of a midwife, care of ongoing and Partnered with women can suppress violence in orphanages. The Government needs to provide training to Midwives on counselling skills, build interpersonal relations, and effective leadership in Midwifery services.